Cretaceous fossil gecko hand reveals a strikingly modern scansorial morphology: Qualitative and biometric analysis of an amber-preserved lizard hand - Fontanarrosa, Gabriela (2018)
Gekkota (geckos and pygopodids) is a clade thought to have originated in the Early Cretaceous and that today exhibits one of the most remarkable scansorial capabilities among lizards. Little information is available regarding the origin of scansoriality, which subsequently became widespread and diverse in terms of ecomorphology in this clade. An undescribed amber fossil (MCZ R–190835) from mid-Cretaceous outcrops of the north of Myanmar dated at 99 Ma, previously assigned to stem Gekkota, preserves carpal, metacarpal and phalangeal bones, as well as supplementary climbing structures, such as adhesive pads and paraphalangeal elements. This fossil documents the presence of highly specialized adaptive structures. Here, we analyze in detail the manus of the putative stem Gekkota. We use morphological comparisons in the context of extant squamates, to produce a detailed descriptive analysis and a linear discriminant analysis (LDA) based on 32 skeletal variables of the manus. The comparative sample includes members of 15 extant squamate families (Agamidae, Dactyloidae, Iguanidae, Leiosauridae, Liolaemidae, Polychrotidae, Tropiduridae, Diplodactylidae, Eublepharidae, Gekkonidae, Phyllodactylidae, Sphaerodactylidae, Gymnophthalmidae, Teiidae, and Scincidae). Although the fossil manus is qualitatively more similar to that of members of Gekkota, the LDA analysis places it in a morphozone shared by Gekkota and Scincomorpha. This result is particularly interesting, given that despite the presence of paraphalangeal structures had only been reported in extant geckos of the families Gekkonidae and Phyllodactylidae, the usage of an adhesive subdigital system to climb originated independently in Gekkota, Scincidae, and Dactyloidae.